Negative electrode binder, negative electrode sheet, and battery
Patent Information
- Application Number
- CN202611237631.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
本申请提供的负极粘结剂,包括核体和壳层,所述壳层设置在所述核体外表面并至少部分包覆所述核体,所述核体包括第一聚合物,所述壳层包括第二聚合物,所述第一聚合物包括共轭二烯结构单元和烯基芳香类结构单元,所述第二聚合物包括离子型结构单元、刚性结构单元以及脂环胺基丙烯酰胺类结构单元;其中,核体的第一聚合物提供基础粘结力;壳层引入离子型结构单元、刚性结构单元及脂环胺基丙烯酰胺类结构单元,其中刚性结构单元能够显著提升乳胶粘结剂的乳胶颗粒整体硬度以及抗挤压能力,辊压加工时可有效抑制乳胶粒子被挤压后发生的坍塌团聚,减少负极中石墨颗粒的表面包覆覆盖面积,弱化锂离子传导阻隔层,进而降低锂离子传输阻力;离子型结构单元可提升乳胶粘结剂的水分散稳定性,无需额外添加分散剂,规避杂质引入对电化学性能的负面影响;脂环胺基丙烯酰胺类结构单元可与刚性单元协同调控壳层力学性能,在强化颗粒抗坍塌刚性的同时平衡粘结韧性。
Smart Images

Figure CN122889758A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery technology, specifically relating to a negative electrode binder, a negative electrode sheet, and a battery. Background Technology
[0002] In lithium-ion batteries, graphite anodes commonly use latex binders (SBR, CMC) to bond graphite powder. However, during electrode rolling, ordinary latex particles (SBR, CMC) are prone to collapse under pressure, which increases the surface area of graphite and forms a dense barrier layer, increasing the resistance to lithium-ion transport. Currently, the industry mainly addresses these issues by optimizing the stirring process and adding dispersants, but the improvement is limited and cannot fundamentally solve the problem of poor dispersion stability in SBR batteries. Furthermore, adding dispersants easily introduces impurities, affecting the battery's electrochemical performance and production stability, making it difficult to meet the mass production requirements of high-quality lithium-ion batteries. Summary of the Invention
[0003] To address the problem in existing technologies where latex particles collapse and agglomerate after rolling, increasing the graphite anode coating area and lithium-ion transport resistance, a negative electrode binder, a negative electrode sheet, and a battery are provided.
[0004] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: On one hand, the present invention provides a negative electrode binder comprising a polymer, the polymer comprising a core and a shell, the shell being disposed on the outer surface of the core and at least partially covering the core; The core comprises a first polymer, and the shell comprises a second polymer; The first polymer comprises conjugated diene structural units and alkenyl aromatic structural units, and the second polymer comprises ionic structural units, rigid structural units, and alicyclic amino acrylamide structural units.
[0005] Optionally, in the first polymer, the mass ratio of the conjugated diene structural unit to the alkenyl aromatic structural unit is (30~70):(30~70).
[0006] Optionally, the ionic structural unit is a structural unit obtained by polymerization of ionic monomers, wherein the ionic monomers include one or more of sodium styrene sulfonate, sodium styrene carboxylate, lithium styrene carboxylate, and lithium styrene sulfonate; and / or, The rigid structural unit is a structural unit obtained by polymerization of norbornene monomer, wherein the norbornene monomer includes one or more of the following: 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 7-methyl-2-norbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-propenyl-2-norbornene, 5-phenyl-2-norbornene, 5-norbornene-2-carboxylic acid, 5,6-norbornene dicarboxylic anhydride, 5-hydroxymethyl-2-norbornene, 5-norbornene-2-ylacrylate, 5-norbornene-2-ylmethacrylate, 7-oxa-2-norbornene, and 5-ethylidene-7-oxa-2-norbornene; and / or, The alicyclic aminoacrylamide structural unit is a structural unit obtained by polymerization of alicyclic aminoacrylamide monomers, and the alicyclic aminoacrylamide monomers include one or more of N-(1-adamantyl)acrylamide, N-(2-adamantyl)acrylamide, N-(1-adamantyl)methylacrylamide, N-(1-adamantyl)-N-methylacrylamide, N-(tricyclodecyl)acrylamide, N-(norbornyl)acrylamide, N-(cubalkyl-1-yl)acrylamide, and N-(perfluoroadamantyl)acrylamide.
[0007] Optionally, in the second polymer, the mass ratio of the ionic structural unit, the rigid structural unit, and the alicyclic aminoacrylamide structural unit is (10~40):(10~50):(10~50).
[0008] Optionally, in the negative electrode binder, the mass ratio of the core to the shell is (70~95):(5~30).
[0009] Optionally, the glass transition temperature of the polymer is -10 to 20°C.
[0010] Optionally, the negative electrode binder further includes a solvent, the solid content of the negative electrode binder is 40%~50%, and the volume average particle size D of the polymer in the negative electrode binder is... 50 The wavelength is 120~150nm.
[0011] Optionally, the absolute value of the zeta potential of the negative electrode binder is greater than 40mV.
[0012] On the other hand, the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer is prepared from a negative electrode slurry comprising the aforementioned negative electrode binder.
[0013] On the other hand, the present invention provides a battery including the aforementioned negative electrode.
[0014] The beneficial effects of this application are as follows: The negative electrode binder provided in this application includes a core and a shell. The shell is disposed on the outer surface of the core and at least partially covers the core. The core includes a first polymer, and the shell includes a second polymer. The first polymer includes conjugated diene structural units and alkenyl aromatic structural units, and the second polymer includes ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units. The first polymer in the core provides basic adhesion. The shell introduces ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units, wherein the rigid structural units... It can significantly improve the overall hardness and extrusion resistance of latex particles in latex binders. During roll forming, it can effectively inhibit the collapse and agglomeration of latex particles after extrusion, reduce the surface coating area of graphite particles in the negative electrode, weaken the lithium-ion conduction barrier layer, and thus reduce the lithium-ion transport resistance. The ionic structural unit can improve the water dispersion stability of the latex binder without the need for additional dispersants, avoiding the negative impact of impurities on electrochemical performance. The alicyclic aminoacrylamide structural unit can synergistically regulate the shell mechanical properties with the rigid unit, balancing the bonding toughness while strengthening the particle's anti-collapse rigidity.
[0015] That is, the negative electrode binder provided in this application utilizes ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units in the shell to maintain good peel strength while further preventing the collapse and aggregation of latex particles after compression, thereby improving or reducing the internal resistance of the coated electrode. Attached Figure Description
[0016] Figure 1 This is a microstructure diagram of the negative electrode binder distributed on the graphite surface in Comparative Example 1; Figure 2 This is a microstructure diagram of the negative electrode binder of Example 1 distributed on the graphite surface. Detailed Implementation
[0017] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0018] This invention provides a negative electrode binder comprising a polymer, the polymer comprising a core and a shell, the shell being disposed on the outer surface of the core and at least partially covering the core; The core comprises a first polymer, and the shell comprises a second polymer; The first polymer comprises conjugated diene structural units and alkenyl aromatic structural units, and the second polymer comprises ionic structural units, rigid structural units, and alicyclic amino acrylamide structural units.
[0019] Specifically, the negative electrode binder provided in this application includes a core and a shell. The shell is disposed on the outer surface of the core and at least partially covers the core. The core includes a first polymer, and the shell includes a second polymer. The first polymer includes conjugated diene structural units and alkenyl aromatic structural units, and the second polymer includes ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units. The first polymer in the core provides basic adhesion. The shell introduces ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units, wherein the rigid structural units can exhibit… This technology significantly improves the overall hardness and extrusion resistance of latex particles in the latex binder. During roll forming, it effectively inhibits the collapse and spreading of latex particles after compression, reduces the surface area of graphite particles in the negative electrode, weakens the lithium-ion conduction barrier layer, and thus reduces lithium-ion transport resistance. The ionic structural unit can improve the water dispersion stability of the latex binder, eliminating the need for additional dispersants and avoiding the negative impact of impurities on electrochemical performance. The alicyclic aminoacrylamide structural unit can synergistically regulate the shell mechanical properties with the rigid unit, strengthening the particle's anti-collapse rigidity, balancing the bonding toughness, and ensuring that the electrode has good peel strength.
[0020] That is, the negative electrode binder provided in this application utilizes the synergistic effect of ionic structural units, rigid structural units and alicyclic aminoacrylamide structural units in the shell to improve or reduce the internal resistance of the coated electrode.
[0021] In some embodiments, the mass ratio of the conjugated diene structural unit to the alkenyl aromatic structural unit in the first polymer is (30~70):(30~70).
[0022] The conjugated diene structural unit is a structural unit formed by the polymerization of conjugated diene monomers, and the alkenyl aromatic structural unit is a structural unit formed by the polymerization of alkenyl aromatic monomers. Among them, conjugated diene monomers include, but are not limited to, one or more of butadiene (BD), isoprene, and 1,3-pentadiene; Alkenyl aromatic monomers include, but are not limited to, one or more of styrene, α-methylstyrene, vinyltoluene, and divinylbenzene.
[0023] Specifically, limiting the mass ratio of conjugated diene structural units to alkenyl aromatic structural units in the first polymer to the range of (30~70):(30~70) is beneficial for better controlling the flexibility, elastic modulus, and bonding performance of the core matrix, so as to further adapt to the coating, rolling, and battery charging and discharging deformation requirements of the negative electrode sheet. Among them, the conjugated diene structural units have excellent flexibility and elasticity. When the proportion is within the above range, the binder core can have good deformation adaptability, buffer the volume expansion and contraction of graphite particles during lithium insertion and extraction, effectively alleviate the stress concentration of active materials, and avoid electrode sheet cracking and powder shedding; while the alkenyl aromatic structural units are rigid aromatic ring structures, which can improve the structural strength, cohesion, and temperature stability of the core. In this application, the synergistic effect of conjugated diene structural units and alkenyl aromatic structural units within the above-mentioned ratio range is utilized. This avoids the problem of excessively high alkenyl aromatic monomer content leading to an overly rigid core and insufficient flexibility, and also solves the problem of excessively high conjugated diene monomer content leading to low core strength, insufficient adhesion, and loose structure after electrode rolling. As a result, the binder core has both high-strength adhesion and excellent deformation adaptability, ensuring the long-term structural stability of the negative electrode.
[0024] Furthermore, the mass ratio of the conjugated diene structural unit to the alkenyl aromatic structural unit includes, but is not limited to, 30:70, 40:60, 50:50, 60:40, and 70:30.
[0025] In some embodiments, the ionic structural unit is a structural unit obtained by polymerization of ionic monomers, wherein the ionic monomers include one or more of sodium styrene sulfonate, sodium styrene carboxylate, lithium styrene carboxylate, and lithium styrene sulfonate; and / or, The rigid structural unit is a structural unit obtained by polymerization of norbornene monomer, wherein the norbornene monomer includes one or more of the following: 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 7-methyl-2-norbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-propenyl-2-norbornene, 5-phenyl-2-norbornene, 5-norbornene-2-carboxylic acid, 5,6-norbornene dicarboxylic anhydride, 5-hydroxymethyl-2-norbornene, 5-norbornene-2-ylacrylate, 5-norbornene-2-ylmethacrylate, 7-oxa-2-norbornene, and 5-ethylidene-7-oxa-2-norbornene; and / or, The alicyclic aminoacrylamide structural unit is a structural unit obtained by polymerization of alicyclic aminoacrylamide monomers, and the alicyclic aminoacrylamide monomers include one or more of N-(1-adamantyl)acrylamide, N-(2-adamantyl)acrylamide, N-(1-adamantyl)methacrylamide, N-(tricyclodecyl)acrylamide, N-(norbornyl)acrylamide, N-(cubalkyl-1-yl)acrylamide, and N-(perfluoroadamantyl)acrylamide.
[0026] Specifically, in this embodiment, the monomers of the ionic structural unit, rigid structural unit, and alicyclic aminoacrylamide structural unit are further defined. The ionic structural unit is polymerized from ionic monomers such as sodium styrene sulfonate. These monomers can be rapidly ionized in the aqueous negative electrode slurry system, forming a uniform and high-density negatively charged adsorption layer on the surface of SBR particles. This significantly enhances the electrostatic repulsion between particles, effectively counteracts the van der Waals adsorption force between traditional particles, and inhibits spontaneous aggregation and flocculation of particles from a kinetic perspective, thereby improving the storage stability and coating uniformity of the aqueous slurry. The rigid structural unit is obtained by polymerization of various substituent-modified norbornene monomers. These monomers all contain a rigid bicyclic alicyclic skeleton. After polymerization, a stable rigid structure can be introduced into the shell, which greatly improves the overall mechanical strength and resistance to compression deformation of the particles, avoids the collapse and spreading deformation of the particles during the electrode rolling and hot pressing processes, and prevents the particles from covering the graphite active sites and blocking the lithium ion transport channels. Alicyclic aminoacrylamide structural units are polymerized from monomers such as adamantyl, tricyclic decyl, or cubic alkyl. These monomers have large volume and skeletal structure, and strong steric hindrance effect. They can build a stable three-dimensional spatial barrier on the surface of latex adhesive particles, effectively preventing latex particles from entangled, adhering, and agglomerating. This solves the problem of particle agglomeration from a spatial structure perspective. At the same time, the porous nature of the skeletal structure can slightly optimize the interfacial pore structure, which is beneficial for electrolyte wetting and lithium ion migration.
[0027] In some embodiments, the mass ratio of the ionic structural unit, the rigid structural unit, and the alicyclic aminoacrylamide structural unit in the second polymer is (10~40):(10~50):(10~50).
[0028] Specifically, the mass ratio of ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units in the second polymer is further limited to the range of (10~40):(10~50):(10~50). The proportion of ionic structural units, controlled within the range of 10~40, ensures sufficient negative charge density on the surface of the particles, forming an effective electrostatic repulsion effect. Simultaneously, it avoids excessively high proportions of ionic units, which could lead to excessive hydrophilicity, abnormal viscosity, and imbalanced coating and drying rates, causing electrode cracking. The proportion of norbornene rigid structural units, at 10~50, improves the mechanical strength of the particles, meeting the requirements of the roller... The compression and hot-pressing processes require resistance to deformation, while avoiding excessive rigidity that could lead to excessive shell brittleness and easy breakage of the bonding interface. The proportion of alicyclic aminoacrylamide structural units is 10-50%, which can build sufficient steric barrier to inhibit particle agglomeration, while avoiding the problems of uneven shell coating, large particle size, and reduced slurry dispersibility caused by an excessive proportion of this structural unit. That is, the three structural units in the second polymer work synergistically within this ratio range, so that the shell has excellent electrostatic dispersibility, structural rigidity and steric anti-agglomeration ability, thereby solving the problems of negative electrode coating defects and their impact on battery electrochemical performance.
[0029] Furthermore, the mass ratio of the ionic structural unit, the rigid structural unit, and the alicyclic aminoacrylamide structural unit includes, but is not limited to, 20:10:40, 20:40:10, 20:50:30, 30:10:20, 30:50:10, 10:20:10, 20:10:30, 20:40:50, 30:10:50, and 40:20:40.
[0030] In some embodiments, the mass ratio of the core to the shell in the negative electrode binder is (70~95):(5~30).
[0031] Specifically, based on previous related tests, it was found that when the mass ratio of the core to the shell in the negative electrode binder is limited to (70~95):(5~30), the binding performance of the binder can be better balanced and its application in the battery can improve the electrochemical performance. Among them, the core body, as the main body of the adhesive, has a proportion of 70-95% to ensure the excellent overall adhesion and flexibility of the adhesive, firmly fix the negative electrode active particles, ensure the mechanical properties of the electrode, and avoid diluting the adhesive matrix and reducing the interfacial bonding strength due to an excessive proportion of the functional shell layer. A shell layer ratio of 5-30% can form a uniform and complete functional coating layer on the core surface, giving full play to the modification effects of electrostatic repulsion, steric hindrance, and rigid deformation resistance, and effectively solving the problems of particle agglomeration and electrode pitting. At the same time, this ratio range can avoid insufficient functional structural units due to an excessively thin shell layer, and can also avoid the situation where the particle size of the particles increases, the viscosity of the slurry increases, and the leveling properties of the coating deteriorate due to an excessively thick shell layer.
[0032] Furthermore, the mass ratio of the core to the shell includes, but is not limited to, 70:30, 80:20, 85:15, 90:10, 75:25, 82:18, 90:20, or 95:5.
[0033] In some embodiments, the glass transition temperature (Tg) of the polymer is -10 to 20°C.
[0034] Specifically, by further limiting the glass transition temperature Tg, the binder can remain flexible under room temperature coating and rolling processes, enabling it to adhere to the surface of graphite particles, fill the gaps between particles, improve the flatness of the electrode, and prevent the formation of pores and pits in the electrode. At the same time, under the environment of battery charging and discharging, the binder will not undergo glass hardening or excessive softening in a high-elastic state. This avoids both low-temperature hardening leading to electrode brittleness and poor interfacial contact, and high-temperature softening and creep leading to particle agglomeration and increased internal resistance. In other words, a stable glass transition temperature can ensure the structural stability of the binder and better maintain its excellent anti-agglomeration ability and interfacial adhesion performance.
[0035] In some embodiments, the negative electrode binder further includes a solvent, the solid content of the negative electrode binder is 40%~50%, and the volume average particle size D of the polymer in the negative electrode binder is... 50 The wavelength is 120~150nm.
[0036] The solid content of the negative electrode binder is limited to 40%~50%, and the volume average particle size D of the polymer is... 50 Maintaining the nanometer size within the range of 120-150 nm is beneficial for achieving optimal matching between the processing performance of the negative electrode slurry and the forming quality of the electrode sheet. Specifically, maintaining the solid content within the range of 40%-50% can improve coating efficiency, reduce solvent evaporation, and mitigate problems such as particle migration, agglomeration, and surface pinholes caused by rapid solvent evaporation during electrode drying, while ensuring good slurry flowability and coating leveling properties. It also adapts to high-speed coating processes and improves the production yield of the electrode sheet.
[0037] The volume average particle size D of the polymer 50 Controlling the particle size within the 120-150 nm range ensures high dispersion of the polymer particles in the aqueous slurry, resulting in uniform particle size and sufficient specific surface area. This allows for uniform coating of the graphite active particles, preventing the accumulation of large-diameter particles and the formation of electrode defects. Simultaneously, the polymer's volume average particle size D... 50 A negative electrode binder with a diameter of 120~150nm can fill the gaps between graphite particles, optimize the pore structure of the electrode, improve the electrolyte wetting efficiency, shorten the lithium-ion transport path, and reduce the internal resistance of the battery, thereby achieving a balance between the flatness and density of the electrode structure and the electrochemical transport performance after application.
[0038] Furthermore, one embodiment of this application provides a method for preparing a negative electrode binder, comprising the following steps: Add 105 parts of deionized water, 0.05 parts of emulsifier (sodium dodecylbenzenesulfonate), 40 parts of styrene (alkenyl aromatic monomer), and 30 parts of butadiene (conjugated diene monomer) to the reactor. After high-speed stirring and pre-emulsification, nitrogen gas is introduced to drive out the active oxygen in the reactor. Then, 0.1 parts of initiator (sodium persulfate) are added, and polymerization is carried out at 50~70℃ for 3 hours to obtain the initial core emulsion. Add 3 parts of ionic monomer, 1.5 parts of norbornene monomer, and 6 parts of alicyclic aminoacrylamide monomer to the core emulsion, add 0.05 parts of emulsifier and 10 parts of deionized water, heat to 80~90℃ and polymerize for 3 hours to form core-shell structured emulsion particles. After polymerization, cool down and adjust pH to 8. Filter to remove gel or coarse particles to obtain negative electrode binder emulsion.
[0039] As those skilled in the art know, the reactions in the above steps are conventional free radical polymerization, and the specific methods and reaction conditions are common free radical polymerization methods in the prior art, which will not be described in detail in this invention.
[0040] In this invention, each of the aforementioned structural units represents the structural portion of the monomer that exists in the resulting polymer after the monomer participates in the polymerization reaction; The mass ratio of each structural unit is based on the mass ratio of the corresponding monomer in the total amount of monomers participating in the polymerization. Similarly, the aforementioned mass ratio of the core to the shell is based on the ratio of the total mass of monomers when preparing the core to the total mass of monomers when preparing the shell.
[0041] In some embodiments, the absolute value of the zeta potential of the negative electrode binder is greater than 40 mV.
[0042] It should be noted that the absolute value of the Zeta potential is the core indicator characterizing the stability of colloidal dispersion systems. This scheme limits the absolute value of the Zeta potential of the binder to greater than 40mV, giving the binder slurry excellent dispersion stability.
[0043] Specifically, when the absolute value of the Zeta potential is higher than 40mV, the polymer surface in the negative electrode binder has a very high degree of negative charge enrichment, and the electrostatic repulsion potential energy between the particles is much greater than the van der Waals attraction potential energy. This can overcome the defects of spontaneous aggregation and flocculation of the particles, and keep the binder in a uniformly dispersed state of single particles throughout the entire process of slurry stirring, standing, and coating. This avoids defects such as pits, pinholes, and uneven thickness of the electrode sheet caused by particle aggregation. At the same time, the high Zeta potential can improve the interfacial compatibility between the binder and the graphite particles, so that the binder is uniformly adsorbed on the surface of the active particles, avoiding local enrichment or absence of binder, ensuring the uniform and stable structure of the negative electrode active material layer, and effectively reducing the polarization degree of the cell.
[0044] Another embodiment of the present invention provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer is prepared from a negative electrode slurry including the aforementioned negative electrode binder.
[0045] Specifically, the negative electrode sheet includes the negative electrode binder provided in this application, which utilizes the synergistic effect of ionic structural units, rigid structural units and alicyclic aminoacrylamide structural units in the shell to improve or reduce the internal resistance of the coated electrode sheet.
[0046] Another embodiment of the present invention provides a battery including the aforementioned negative electrode sheet, wherein the battery is equipped with the aforementioned negative electrode sheet, which is beneficial to reducing the internal resistance of the battery.
[0047] The present invention will be further illustrated by the following examples.
[0048] Example 1 This embodiment illustrates a negative electrode binder, negative electrode sheet, and battery disclosed in this invention. The specific preparation process includes the following steps: Preparation of negative electrode binder 105 parts deionized water, 0.05 parts emulsifier (sodium dodecylbenzenesulfonate), 40 parts styrene (alkenyl aromatic monomer), and 30 parts butadiene (conjugated diene monomer) were added to a reaction vessel. After pre-emulsification by high-speed stirring, nitrogen gas was introduced to remove active oxygen from the reaction vessel. Then, 0.1 parts initiator (sodium persulfate) was added, and the reaction was carried out at 60°C for 3 hours to obtain a core emulsion. Three parts of ionic monomer, 1.5 parts of norbornene monomer, and 6 parts of alicyclic aminoacrylamide monomer were added to the core emulsion. 0.05 parts of emulsifier and 10 parts of deionized water were added, and the mixture was heated to 85°C and reacted for 3 hours to obtain a core-shell structured SBR. After polymerization, the mixture was cooled and the pH was adjusted to 8. Filter to remove gel or coarse particles to obtain negative electrode binder emulsion; The mass ratio of ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units is 20:10:40; In the negative electrode binder, the mass ratio of the core to the shell is 70:30.
[0049] Preparation of negative electrode sheet 1.5 parts carboxymethyl cellulose (CMC), 1 part conductive agent Super P, and 96 parts graphite were dispersed in water, and then 1.5 parts negative electrode binder emulsion were added and dispersed to obtain a negative electrode slurry. The negative electrode slurry is coated onto copper foil, dried, and then cut to obtain the negative electrode sheet.
[0050] Battery manufacturing After assembling the negative electrode, separator, and NCM811 positive electrode into a dry cell, the battery is obtained by injecting electrolyte. The electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a 1:1 mass ratio, and then LiPF6 is added until the molar concentration is 1.0 mol / L.
[0051] Examples 2-35 Examples 2-35 illustrate the negative electrode binder, negative electrode sheet, and battery disclosed in this invention, and include most of the operations in Example 1, except that: The formulations of the adhesives in Examples 2 to 35 are all based on Table 1.
[0052] Comparative Examples 1-7 Comparative Examples 1-7 are used to compare and illustrate the negative electrode binder, negative electrode sheet, and battery disclosed in this invention, including most of the operations in Example 1, except that: The formulations of the adhesives in Comparative Examples 1 to 7 are all based on Table 1.
[0053] It should be noted that, except for the contents listed in Table 1, the other preparation conditions are the same as those in Example 1, and the solid content of all examples and the comparative system is kept the same. During the batching stage, the amount of deionized water added will be adjusted according to the differences in the amount of each group of materials, so as to offset the solid content fluctuation caused by the change in the amount of the formula components and eliminate the interference caused by the different solid content on the performance test results of the negative electrode binder.
[0054] Table 1 Continued from Table 1 Continued from Table 1 contrast Figure 1 (Comparative Example 1) and Figure 2 The microstructure of the graphite anode in Example 1 can be clearly seen. Figure 1The negative electrode binder provided in Comparative Example 1, after being rolled, exhibits a large-scale collapse and aggregation of latex particles, which extensively covers the surface of the graphite particles, blocking lithium-ion transport channels and increasing the internal resistance of the electrode. Figure 2 The core-shell structured negative electrode binder provided in this application relies on the synergistic effect of the rigid shell structural unit, the ionic structural unit, and the alicyclic aminoacrylamide structural unit. The particles are not easily compressed and collapse and are evenly dispersed, and the graphite active sites are fully exposed, ensuring smooth lithium-ion conduction. This microscopically confirms that the binder can reduce the electrode resistance.
[0055] Performance testing Batteries were prepared using the negative electrode binders obtained in Examples 1-35 and Comparative Examples 1-7, and the performance of the negative electrode binders and batteries was tested as follows: 1. Solid content detection: Weigh 1-2 grams of the prepared negative electrode binder emulsion, bake it in an oven at 120℃ for 4 hours, and then weigh it. The weight after drying / the initial weight is the solid content.
[0056] 2. Polymer volume average particle size D 50 Detection: Polymer volume average particle size D 50 The final prepared negative electrode binder emulsion was used as the test object. Before testing, the negative electrode binder emulsion to be tested was diluted with deionized water to a suitable concentration to meet the testing requirements of laser particle size analyzer or dynamic light scattering particle size analyzer; refractive index 1.596, absorptivity 0.01; test temperature 25℃, each sample was tested in parallel at least 3 times, and the median particle size in the volume distribution or intensity distribution was taken as D. 50 The average value of multiple test results is used as the D value for the corresponding sample. 50 .
[0057] 3. Methods for determining the glass transition temperature (Tg) of polymers: The negative electrode binder emulsion to be tested was dried to constant weight at 60℃~80℃ to obtain a dried polymer sample. The glass transition temperature (Tg) of the dried polymer sample was detected using a differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100). The steps included: turning on high-purity nitrogen, setting the nitrogen flow rate to 0.5L / min~0.6L / min, turning on the DSC power, and running the desktop; setting the temperature to -100℃, holding at that temperature for 10 min, with a temperature range of -100℃~180℃, and a heating rate of 10K / min; after setting, placing the prepared sample on the heating furnace, covering the furnace with the protective cover, adding an appropriate amount of liquid nitrogen to the constant temperature container, and running the test when the sample temperature reached -100℃. The glass transition temperature of the corresponding sample was determined based on the glass transition range in the DSC curve. The glass transition temperature of the polymer was measured using the polymer sample after the final drying of the negative electrode binder emulsion.
[0058] 4. Detection of absolute value of Zeta potential: The zeta potential was tested using electrophoretic light scattering (ELS / Laser Doppler). The negative electrode binder emulsion was diluted to a low concentration with deionized water or slurry supernatant and injected into a folded capillary zeta cell. An alternating electric field was applied to cause the charged particles to undergo laser Doppler frequency shift during electrophoresis. The sliding surface zeta potential was calculated from the electrophoretic mobility using the Smoluchowski equation.
[0059] 5. Peel strength test: The coated single-sided negative electrode sheet was prepared at a ratio of 1.6 g / cm². 3 After compaction, the electrode is cut into 20cm long x 3cm wide pieces. 3M double-sided tape is attached to the steel plate, and the coated side of the electrode is fixed to the tape on the steel plate with the coated side facing down. After rolling back and forth 6 times with a 2.5kg roller, a tensile testing machine with a range of 40 N is used. The upper plate clamps the copper foil side, and the coating and copper foil are torn apart at a speed of 50 mm / min and a 180° stretch. The data of the stable tensile section is recorded as the peel strength (N / m).
[0060] 6. DCIR Test: ① After fully charging the battery at 25℃ with constant current and constant voltage (4.35V, 0.05C) at 0.5C, leave it at the ambient temperature to be tested for 8 hours, and discharge it at constant current at 0.5C to 2.75V (2.5V at 0℃). Record the discharge capacity at this temperature, and use it as the reference capacity Qt for the next pulse test. ② After fully charging the battery at 25℃ with constant current and constant voltage (4.35V, 0.05C) at 0.5C, let it stand for 8 hours at the ambient temperature to be tested. After discharging 2 / 10*Qt of capacity with constant current at 1C, the SOC is 80%. Let it stand for 1 hour, and then discharge it with 3C for 30 seconds. Then discharge it with constant current at 1C, adjust the SOC to 50% and 20%, and then let it stand for 1 hour. Then discharge it with 3C for 30 seconds. Calculate the DCIR at 20%, 50%, and 80% SOC.
[0061] The test results are entered into Table 2.
[0062] Table 2 As can be seen from the test results in Table 2, in Examples 1-3, the mass ratio of the conjugated diene structural unit to the alkenyl aromatic structural unit in the first polymer of the core was changed to 30:40, 40:60, and 70:30, respectively. Specifically, in the test results, the absolute value of the Zeta potential in Examples 1-3 remained stable at 40 mV. 50 The results for solid content were relatively consistent, while the results for Tg, peel strength, and DCIR showed differences. Specifically, when the proportion of conjugated diene structural units increased (Example 3), the binder Tg rose to 10°C, the peel strength slightly decreased to 12 N / m, and the DCIR decreased to 48 mΩ; when the proportion of alkenyl aromatic structural units increased (Example 2), the Tg dropped to -3°C, and the peel strength increased to 12.8 N / m. This indicates that alkenyl aromatic structural units in the core can increase the flexibility of the binder and the peel force of the electrode, while conjugated diene structural units can improve the rigidity of the core and reduce the DC internal resistance of the electrode.
[0063] Examples 4-9 show variations in the ratio of three structural units: ionic structural units, rigid structural units, and alicyclic aminoacrylamide units. In the corresponding test results, the polymer Tg was between 0 and 7°C, and the absolute value of the Zeta potential was not lower than 40 mV. As the proportion of rigid units and alicyclic aminoacrylamide units increased, and the proportion of ionic units decreased, the electrode peel strength continuously decreased, and the DCIR decreased simultaneously. It is speculated that this is because rigid structural units can enhance the compressive strength of the particles and reduce graphite surface coating, thereby reducing the internal resistance of ion transport. However, an excessive number of alicyclic aminoacrylamide structural units weakens the shell bonding toughness and lowers the peel strength. This indicates that the ratio of ionic structural units, rigid structural units, and alicyclic aminoacrylamide units within the (10-40):(10-50):(10-50) range specified in this application can simultaneously ensure both low internal resistance of the battery after application and electrode peel strength that meets usage requirements.
[0064] The core-shell mass ratios in Examples 10-13 were 80:20, 75:25, 82:18, and 95:5, respectively. Test results showed that as the core proportion increased and the shell proportion decreased, the polymer's Tg gradually decreased (Tg 2℃ in Example 1, Tg -2.5℃ in Example 13), while the peel strength continuously increased, and the DCIR also increased synchronously. A higher shell proportion resulted in sufficient surface-modified functional unit content, better particle anti-collapse and dispersion effects, and lower electrode internal resistance. However, excessive shell dilutes the core matrix, leading to a decrease in peel strength. When the shell proportion decreased to 5% (Example 13), the proportion of the core-bonded body significantly increased, resulting in optimal electrode peel strength. However, insufficient functional shell coating caused the particles to easily spread and cover graphite after rolling, significantly increasing the DC internal resistance.
[0065] In Example 1, the ionic monomer was sodium styrene sulfonate; in Example 14, it will be replaced with sodium styrene carboxylate. Both groups of D... 50 There were no significant differences in Tg, peel strength, and DCIR. Only the absolute value of the Zeta potential increased slightly from 40mV to 42mV, indicating that both sodium styrene sulfonate and sodium styrene carboxylate, two types of ionic monomers, can form a high-density negatively charged layer on the surface of the granules, effectively improving the dispersion stability of the slurry. The mechanical properties and internal resistance of the binder after replacement were not significantly affected. That is, it shows that the same effect can be achieved by using different ionic monomers as defined in this application.
[0066] Examples 15-28 changed the specific material selection of norbornene monomers used in the rigid structural unit. In the corresponding test data, Tg, Zeta potential, peel strength, and DCIR were not significantly different from those in Example 1, proving that the polymerization of norbornene monomers within the scope of this application can introduce a bicyclic rigid skeleton into the shell layer, which equally improves the particle's resistance to extrusion and collapse. Substituent alkyl, alkenyl, carboxyl, ester, and oxyheterocyclic structures will not destroy the deformation resistance of the rigid skeleton.
[0067] The specific choices of the alternative alicyclic amino acrylamide monomers in Examples 29-35 show no significant difference in test data compared to Example 1. The only difference is that Example 29 used N-(1-adamantyl)methacrylamide, which reduced its Tg to 1.8℃ and slightly increased its peel strength to 12.7 N / m. This indicates that large-volume alicyclic skeletons such as adamantane, tricyclodecane, cubane, and norbornyl can provide strong steric hindrance and inhibit particle aggregation. The methyl substitution slightly adjusts the shell flexibility without weakening the steric barrier effect. The above further illustrates that various alicyclic amino acrylamide monomers within the scope of this application can achieve the corresponding technical effects.
[0068] Comparative Example 1 has three types of functional units: non-ionic, rigid, and alicyclic amine. Its absolute value of Zeta potential is only 35mV, Tg is -8℃, DCIR is as high as 60mΩ, and its internal resistance is significantly higher than that of all examples. The reason is that after rolling, a large amount of the granules collapse and coat the graphite, which hinders the conduction of lithium ions. Comparative Example 2 only added ionic structural units, lacking rigid structural units and alicyclic amine structural units. The Zeta potential increased to 50mV and the dispersion improved, but there was no rigid framework to resist compression, and the DCIR was still as high as 58mΩ. Comparative Example 3 only has rigid structural units, and Comparative Example 4 only has alicyclic amine structural units. Both have a Zeta potential of only 35mV, and the slurry is prone to agglomeration. Although the rigid units can slightly reduce the internal resistance, they lack electrostatic dispersion stabilization. Comparative Example 5 lacks alicyclic amine structural units, Comparative Example 6 lacks rigid structural units, and Comparative Example 7 lacks ionic structural units. None of the three groups meet the requirements of the second shell polymer as defined in this application. Their peel strength is lower than that of all examples, and their DCIR is higher than that of the examples.
[0069] As can be seen from the above comparative examples, synergistic effects cannot be achieved by using only one or two types of structural units. Only when ionic structural units, rigid structural units, and alicyclic aminoacrylamide structural units are present in the shell can high dispersion stability, particle anti-collapse rigidity, and bonding toughness be achieved simultaneously, while reducing electrode resistance. Adding any one or two types of structural units alone cannot achieve the comprehensive performance of the binder in this application.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A negative electrode binder, characterized in that, The polymer includes a core and a shell, the shell being disposed on the outer surface of the core and at least partially covering the core; The core comprises a first polymer, and the shell comprises a second polymer; The first polymer comprises conjugated diene structural units and alkenyl aromatic structural units, and the second polymer comprises ionic structural units, rigid structural units, and alicyclic amino acrylamide structural units.
2. The negative electrode binder according to claim 1, characterized in that, In the first polymer, the mass ratio of the conjugated diene structural unit to the alkenyl aromatic structural unit is (30~70):(30~70).
3. The negative electrode binder according to claim 1, characterized in that, The ionic structural unit is a structural unit obtained by polymerization of ionic monomers, and the ionic monomers include one or more of sodium styrene sulfonate, sodium styrene carboxylate, lithium styrene carboxylate, and lithium styrene sulfonate; and / or, The rigid structural unit is a structural unit obtained by polymerization of norbornene monomer, wherein the norbornene monomer includes one or more of the following: 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 7-methyl-2-norbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-propenyl-2-norbornene, 5-phenyl-2-norbornene, 5-norbornene-2-carboxylic acid, 5,6-norbornene dicarboxylic anhydride, 5-hydroxymethyl-2-norbornene, 5-norbornene-2-ylacrylate, 5-norbornene-2-ylmethacrylate, 7-oxa-2-norbornene, and 5-ethylidene-7-oxa-2-norbornene; and / or, The alicyclic aminoacrylamide structural unit is a structural unit obtained by polymerization of alicyclic aminoacrylamide monomers, and the alicyclic aminoacrylamide monomers include one or more of N-(1-adamantyl)acrylamide, N-(2-adamantyl)acrylamide, N-(1-adamantyl)methylacrylamide, N-(1-adamantyl)-N-methylacrylamide, N-(tricyclodecyl)acrylamide, N-(norbornyl)acrylamide, N-(cubalkyl-1-yl)acrylamide, and N-(perfluoroadamantyl)acrylamide.
4. The negative electrode binder according to claim 1, characterized in that, In the second polymer, the mass ratio of the ionic structural unit, the rigid structural unit, and the alicyclic aminoacrylamide structural unit is (10~40):(10~50):(10~50).
5. The negative electrode binder according to claim 1, characterized in that, In the negative electrode binder, the mass ratio of the core to the shell is (70~95):(5~30).
6. The negative electrode binder according to claim 1, characterized in that, The glass transition temperature of the polymer is -10 to 20°C.
7. The negative electrode binder according to any one of claims 1 to 6, characterized in that, The negative electrode binder also includes a solvent, and the solid content of the negative electrode binder is 40%~50%. In the negative electrode binder, the volume average particle size D of the polymer is... 50 The wavelength is 120~150nm.
8. The negative electrode binder according to any one of claims 1 to 6, characterized in that, The absolute value of the zeta potential of the negative electrode binder is greater than 40mV.
9. A negative electrode sheet, characterized in that, It includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer is prepared from a negative electrode slurry including the negative electrode binder according to any one of claims 1 to 8.
10. A battery, characterized in that, Includes the negative electrode sheet as described in claim 9.